Quantitative Analysis of Financial Statements Based on Changes, Percentages, and Trends on the Balance Sheet and Expenditure Realization Report of the Directorate General of Forestry Planning and Environmental Management for the Fiscal Year 2019–2024 - Aris Budi Kurniawan; Budi Supriyatno; Azis Hakim (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the quality of the financial statements of the Directorate General of Forestry Planning and Environmental Management in supporting transparency and accountability in budget management for the 2019–2024 Fiscal Year. The analysis is focused on the Balance Sheet and Expenditure Realization Report using a descriptive quantitative approach. The analysis techniques used include the analysis of changes in financial statements (horizontal analysis), percentage analysis per component (vertical analysis), and trend analysis (trend analysis). The results showed that the financial position of the Directorate General of Forestry Planning and Environmental Management during the study period fluctuated, especially in the asset and equity components, while liabilities were at a relatively small level compared to total assets. The rate of realization of expenditure against the budget is consistently above 90 percent, which reflects the effectiveness of budget implementation. Trend analysis shows that the realization of spending tends to increase in the long term, despite fluctuations between budget years. Overall, the results of the analysis indicate that the financial management at the Directorate General of Forestry Planning and Environmental Management has shown a positive direction and is supported by the presentation of consistent and reliable financial statements. Thus, the quality of the financial statements produced has played a role in increasing transparency and accountability in budget management.